2010
DOI: 10.1093/bja/aeq040
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness, safety, and pharmacokinetic and pharmacodynamic characteristics of microemulsion propofol in patients undergoing elective surgery under total intravenous anaesthesia

Abstract: Aquafol was as effective and safe as Diprivan, but caused more severe and frequent injection pain. Aquafol demonstrated similar pharmacokinetics to Diprivan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 27 publications
0
50
0
2
Order By: Relevance
“…reported that the pharmacodynamics and pharmacokinetic properties of this formulation were “substantially similar” to the widely available propofol formulation, but the pain on injection of this nonlipid preparation was a lot more. [11] Another lipid-free preparation of propofol has been developed containing sulfobutylether-ß-cyclodextrin and water, but it does not reduce pain on injection. [12]…”
Section: Different Formulations Of Propofolmentioning
confidence: 99%
“…reported that the pharmacodynamics and pharmacokinetic properties of this formulation were “substantially similar” to the widely available propofol formulation, but the pain on injection of this nonlipid preparation was a lot more. [11] Another lipid-free preparation of propofol has been developed containing sulfobutylether-ß-cyclodextrin and water, but it does not reduce pain on injection. [12]…”
Section: Different Formulations Of Propofolmentioning
confidence: 99%
“…Essa formulação apresenta maior fração livre e menor distribuição tecidual (JUNG et al, 2010), resultado este diferente do observado por MOREY et al (2006a) Não foram observadas diferença entre as ASC no EMU e NANO, assim como descrito por CHO et al (2010). Entretanto, os valores no NANO foram maiores, refl etindo as Cp encontradas em menor distribuição lipídica da nanoemulsão (JUNG et al, 2010).…”
Section: Resultsunclassified
“…This micro-emulsion was found to be equally safe and effective (mean infusion rate-6.2 vs 6.3 mg/kg/hour); it caused more severe injection pain (median VAS 72 mm vs 11.5mm) which was more frequent (81.9% vs 29.2%)and was reported to be associated with a high aqueous free propofol concentration (63.3 vs 12.4 µgm/ml in Diprivan.) [15] 2.2 Other Causes of propofol painImmediate pain due to injection of propofol results from its direct irritant effect. Pain originates from afferent nerve endings between intima and media of the veins via myelinated A-delta fibres.…”
Section: Discussion 21 Different Formulations Of Propofol Derived Fomentioning
confidence: 99%